Estimation of miRNA-21, miRNA-422, miRNA‐142-3p, and miR-181c Gene Expression as Potential Biomarkers of Osteoporosis in Premenopausal Women - Nahidah kzar madhloom; Maan Hasan Salih; Iktefa Abdul Hamid Mohammed saeed; Shimaa Jumaa Abood (Diyala Journal of Medicine)
Background: MicroRNAs (miRNAs) regulate several biological pathways in osteoporosis patients. The study aimed to estimate the correlation of miRNA-21, miRNA-422, miRNA‐142-3p, and miR-181c with osteoporosis in premenopausal women.